Modelling the Correlation Between Preservice Social Studies Teachers’ Perceptions of 21st-Century Skills Competency and Lifelong Learning Tendencies - Aksüt, Selda; Ezer, Feyzullah (ISMAIL HAKKI MIRICI, 2025)
This study aims to model the correlation between the perceptions of preservice social studies teachers of 21st-century skills competencies and their lifelong learning tendencies. In the study, the correlational survey model was used. The sample consisted of 2850 preservice teachers who were studying in the first, second, third, and fourth years in the Department of Social Studies Education at the Faculty of Education of 15 University in the academic year 2021-2022. The sample was identified by stratified sampling method. A “Personal Information Form,” “21st Century Skills Competency Perceptions Scale,” and “Lifelong Learning Tendencies Scale” were used to collect data. It was concluded that the latent variables of learning and innovation skills, life and career skills and information, media, and technology skills of the perceptions of preservice social studies teachers on the 21st-century skills competency were significant predictors of the latent variables’ determination and curiosity, organization of learning and motivation of lifelong learning tendencies and positively affected them. The activities that are planned to be organized at the university to develop 21st century skills competency perceptions and lifelong learning tendencies should be based on the interests and needs of preservice teachers, and they should be motivated to participate in these activities. © 2025 by International Online Journal of Education and Teaching (IOJET).
Keywords: 21st century skills; Lifelong learning; Pre-service teachers; Social studies